Health Economics and Equity in Preconception Health Care: A Systematic Review - Carrandi, Alayna; Bull, Claudia; Callander, Emily (Seminars in Reproductive Medicine, 2022)
Poor pregnancy outcomes affect a child's lifelong health and disadvantaged populations are at higher risk of poor pregnancy outcomes. Preconception care aims to improve pregnancy outcomes by managing conditions and risks prior to conception. Given known inequities in pregnancy outcomes, the adoption of preconception care may benefit disadvantaged populations. Health economics plays an important role in the implementation of interventions, as economic evaluations seek to identify the most efficient and equitable care options. This review aimed to identify the cost-effectiveness of preconception care and how equity has been considered in these evaluations. A systematic review of literature published between 2012–2022 was undertaken to identify studies that evaluate the economic outcomes of preconception care. Studies that met the inclusion criteria were manually searched for consideration of equity in the economic evaluation analysis. Costs were presented and a narrative synthesis of studies reporting on outcomes of equity was conducted. Eight studies met the inclusion criteria, and only two reported on aspects of equity, specifically ethnicity. Considering the significant disparities in pregnancy outcomes among disadvantaged populations, aspects of equity are important to consider when implementing and evaluating preconception interventions. Therefore, it is recommended that future research focuses on the cost-effectiveness of preconception care and that these evaluations incorporate aspects of equity.
Keywords: preconception; health equity; health economics; cost-effectiveness